1999
DOI: 10.1007/s004360050545
|View full text |Cite
|
Sign up to set email alerts
|

Changes in peripheral blood lymphocyte subpopulations and parasite-specific antibody responses in Trypanosoma evansi infection of sheep

Abstract: This paper reports on changes in the lymphocyte composition of the peripheral blood in sheep infected with Trypanosoma evansi. In addition, parasite-specific IgG1 and IgM antibody responses were monitored using a double-sandwich enzyme-linked immunosorbent assay (ELISA) technique. Eight sheep were infected with 2 x 10(6) T. evansi TREU 2143. The infection was characterised by chronicity and ended in self-cure in two of the sheep. These two sheep were designated group A, whereas the other six sheep, which remai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Therefore, we cloned the field isolates of T. evansi from infected water buffaloes and performed virulence assessment tests using mice and cattle. There have been some reports about the virulence assessment of field isolates of trypanosomes using rodents or ruminant (de Menezes et al 2004; Holzmuller et al 2008; Masumu et al 2006; Onah et al 1999; Onah et al 1996). However, there have been few reports about the virulence assessment tests using both livestock and rodents.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we cloned the field isolates of T. evansi from infected water buffaloes and performed virulence assessment tests using mice and cattle. There have been some reports about the virulence assessment of field isolates of trypanosomes using rodents or ruminant (de Menezes et al 2004; Holzmuller et al 2008; Masumu et al 2006; Onah et al 1999; Onah et al 1996). However, there have been few reports about the virulence assessment tests using both livestock and rodents.…”
Section: Discussionmentioning
confidence: 99%
“…In experimentally infected sheep, dissection of the immune components involved in T. evansi -induced immunosuppression highlighted that macrophages but not CD8(+) T cells were mainly responsible for suppression [189]. Actually, in terms of lymphocyte populations it was shown that an increase in the CD4 : CD8 ratio and IgG1 was associated with self-cure in T. evansi -infected sheep, whereas a decrease in the CD4 : CD8 ratio and IgM associated with an increase in the number of sIg+, CD45R+, CD1+, a major histocompatibility complex (MHC) II+ circulating B cells, was associated with infection and disease development [186, 190]. …”
Section: Immunosuppressive Effectsmentioning
confidence: 99%
“…Again, upon challenge with T. congolense , the CD4+ T-cell and gamma delta T-cell populations decrease in Boran cattle (susceptible) but not in N'Dama cattle (tolerant) [8]. Similarly, among sheep infected by T. evansi , the most susceptible animals showed a significant decrease in CD4+ T-cells, whereas self-cured animals did not [9]. Recently, when recording daily changes in the mouse haemogram after infection with T. evansi , we observed a remarkable synchrony between the peak of parasitaemia and the nadir of the white blood cell count [10].…”
Section: Introductionmentioning
confidence: 95%